Can Health Equity Coexist With Housing Inequalities? A Contemporary Issue in Historical Context. Issue 4 (July 2014) - Woods, Louis Lee; Shaw-Ridley, Mary; Woods, Charlotte A.
The housing policies established by the Federal Home Loan Bank Board, Federal Housing Administration, and the Veterans Administration transformed the American housing market. However, these policies intentionally excluded communities of color from the postwar American housing boom by defining them as contaminants eroding national property values. Hence, racially restrictive federal housing policies established an inequitable generational trajectory for residents in communities across the United States. Public health practitioners are faced with the monumental challenge of addressing health disparities that were in part created by non–public health policies. The purpose of this article is to examine how federal housing policies historically contributed to creating the built environment and therefore establishing a foundation for health disparities. These pervasive, exclusionary policies and the generational stigma associated with this issue raise serious questions about the ethics of contemporary policies, practices, and research aimed at achieving health equity.